Annual layer counting using pollen grains of the Grigoriev ice core from the Tien Shan Mountains, central Asia - Nozomu Takeuchi; Shuntaro Sera; Koji Fujita; Vladimir B. Aizen; Jumpei Kubota (Arctic, Antarctic, and Alpine Research, 2019)
Pollen grains are commonly found in ice cores, particularly those from mountain glaciers at low to middle latitudes. Because the release of pollen from flowers has a seasonality and varies among the plant species, pollen concentrations in ice cores are useful for distinguishing annual or seasonal layers and inferring past vegetation near glaciers. We analyzed major pollen grains in an 87-m-deep ice core drilled at the top of the Grigoriev Ice Cap (4563 m.a.s.l.) in the Tien Shan Mountains, Kyrgyz Republic. Microscopy showed that mainly five pollen taxa were contained in the ice core. Their abundance fluctuated with the depth of the core, indicating their seasonal deposition on the ice cap, while the seasonality of the stable isotopes was not particularly clear because of melting and refreezing signatures. Based on the pollen profiles, annual layers were determined back in time to 1780 AD at a depth of 63.6 m; at greater depth, they could not be distinguished due to ice layer thinning in the glacier. The pollen assemblages have gradually changed during the last 220 years and were particularly distinctive in the deeper part, suggesting the drastic change of vegetation in this region during the Holocene.